Identification of Intelligent Controls in Developing Anti-Lock Braking System - Rau, Vimal; Ahmad, Fauzi; Hassan, Muhammad Zahir; Hudha, Khisbullah (Universiti Teknikal Malaysia Melaka, 2012)
This paper presents about the development of an Antilock Braking System (ABS) using quarter vehicle model and a control structure is developed to represents an ABS and conventional braking model. Different type of controllers is proposed to develop the ABS model. Antilock braking system (ABS) is an important part in vehicle system to produce additional safety for driver. This system is known as one of the automobile’s active safety. In general, Antilock braking systems have been developed to reduce tendency for wheel lock and improve vehicle control during sudden braking especially on slippery road surfaces. In this paper, to deal with the strong nonlinearity in the design of ABS controller, an intelligent controller has been identified. The controllers such as PID and Fuzzy Logic are proposed to control the stopping distance and longitudinal slip of the wheel. Comparison results between these two controllers generated using Matlab SIMULINK.